On the Measurement of the Income Poverty Rate: the Equivalence Scale across Europe - Martina Mysikova; Tomas Zelinsky (Statistika: Statistics and Economy Journal, 2019)
The methodology used to determine the at-risk-of-poverty rate commonly applied in the European context is often criticised for arbitrary steps in its construction. This study questions the first step – the equivalence scale applied to transform the disposable income of households of different sizes into comparable units. First, we hypothesise that economies of scale are lower in Central-Eastern European countries than in their Western counterparts. We assess the hypothesis using a simple descriptive analysis of the structure of household consumption expenditures based on Household Budget Survey data. Second, we demonstrate the sensitivity of the at-risk-of-poverty rate to an equivalence scale based on the Statistics on Income and Living Conditions data. We identify three different groups of countries according to the sensitivity of the income poverty rate to the relative adult and child household member weights assigned by the equivalence scale. The study contributes to the discussion on defining accurate, country-specific equivalence scales.
Keywords: I32; 330; Central-Eastern Europe; equivalence scale; income poverty rate; sensitivity; Western Europe